Characterization of patients with COPD admitted in pulmonary rehabilitation center. - Neto, João Simão de Melo; Marques, Ana Elisa Zuliani Stroppa; Gomes, Fabiana de Campos (Manual Therapy, Posturology & Rehabilitation Journal, 2014)
Introduction: Chronic Obstructive Pulmonary Disease COPD is a major cause of morbidity and mortality, which is preventable, thus studies that discusses the characterization of a given population are important for investment in treatments and prevention. Objective: Characterize individuals with COPD, admitted to a pulmonary rehabilitation center. Method: Retrospective study, exploratory character of medical records of patients with COPD. Sample consisted of 37 patients diagnosed with COPD and age greater than 20 years. The following variables were analyzed: sex, age, marital status, occupation, diagnosis, main complaint, and cardiovascular risk factors presented by patients during admission. Results: Individuals aged >40 years and history of smoking have a higher prevalence in developing COPD. Pulmonary emphysema is a major pathological condition. The most common main complaint was dyspnea and cardiovascular risk factor was present sedentary lifestyle. Moreover, women with COPD were more likely to have depression than men. Conclusion: This study enabled the characterization of COPD patients, providing the possibility of investing in prevention and treatment